2013
DOI: 10.3389/fncel.2013.00227
|View full text |Cite
|
Sign up to set email alerts
|

Introduction and perspective, historical note

Abstract: P2 nucleotide receptors were proposed to consist of two subfamilies based on pharmacology in 1985, named P2X and P2Y receptors. Later, this was confirmed following cloning of the receptors for nucleotides and studies of transduction mechanisms in the early 1990s. P2X receptors are ion channels and seven subtypes are recognized that form trimeric homomultimers or heteromultimers. P2X receptors are involved in neuromuscular and synaptic neurotransmission and neuromodulation. They are also expressed on many types… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
37
1

Year Published

2014
2014
2020
2020

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 34 publications
(38 citation statements)
references
References 187 publications
0
37
1
Order By: Relevance
“…Most P2X subtypes are expressed in different regions of the central nervous system (CNS). P2X3, P2X2, P2X4, and P2X6 receptors are reported to be involved in neurotransmission and neuromodulation [17,18]. Several P2X subtypes, such as P2X2, P2X3, P2X4, and P2X7, are involved in the reflex activities of guts in rats [19,20].…”
Section: Introductionmentioning
confidence: 99%
“…Most P2X subtypes are expressed in different regions of the central nervous system (CNS). P2X3, P2X2, P2X4, and P2X6 receptors are reported to be involved in neurotransmission and neuromodulation [17,18]. Several P2X subtypes, such as P2X2, P2X3, P2X4, and P2X7, are involved in the reflex activities of guts in rats [19,20].…”
Section: Introductionmentioning
confidence: 99%
“…As a neurotransmitter, ATP plays an important role in regulating the transduction of the visceral pain signal by binding to P2X receptors [15,16], and ATP participates in the regulation of intestinal movement and gastrointestinal secretion. P2X receptors are widely distributed in the body, and they play an important role in the formation, transduction, and regulation of neuropathic pain, inflammatory pain, and visceral pain [17][18][19][20]. Many studies have shown that purinergic (P2X) receptors are involved in pain signal transmission, in which the P2X 3 and P2X 2/3 receptors are the main subtypes [21,22].…”
Section: Introductionmentioning
confidence: 99%
“…The P2X receptors are a family of cation channels gated by extracellular ATP (1,(7)(8)(9) and are involved in many physiological and pathophysiological processes (10)(11)(12). Seven subtypes of the P2X receptors have been identified in mammals (13), and they share ∼40% sequence identity.…”
mentioning
confidence: 99%
“…Each ligand for a ligand-gated ion channel has a distinct ability to evoke currents (1), and the ligands are classified according to the evoked current level: such as, full agonists, partial agonists, and antagonists. Partial agonists of ligand-gated ion channels reportedly offer clinical advantages over antagonists and full agonists in antidepressant and smoking-cessation treatment (2,3).…”
mentioning
confidence: 99%